Molecular and cytogenetic analysis of a familial microdeletion of Xq. Issue 3 (March 1991) - Wells, S; Mould, S; Robins, D; Robinson, D; Jacobs, P
Abstract : Cytogenetic analysis of a male infant referred for poor neurological development and failure to thrive showed a microdeletion of the X chromosome, his karyotype being 46, Y, del(X)(pter----q21.1:: q21.2----qter). His mother and grandmother were also found to carry the deletion. DNA probes were used to define the deletion molecularly and it was shown to span intervals 2 to 6 of Cremers et al, a portion of Xq that contains the TCD gene and genes whose absence is associated with deafness and mental retardation. RFLP analysis together with X inactivation studies using the probe M27 beta verified the carrier status of the female relatives and showed non-random X inactivation in the heterozygous females.